(untitled) (Gumilyov Journal of Pedagogy, 2025)
The article deals with the problem of improving the professional activities of future social pedagogues on the basis of spiritual and moral values. The authors consider the effectiveness of their use in the educational process of higher education institutions, considering it as one direction of formation of professional activities of future social pedagogues on the basis of spiritual and moral values. Currently, as we have seen, the theoretical analysis is mainly based on the views and opinions of Kazakh scholars, public figures and educators on the essence and educational significance of spiritual and moral values. The current demand is that society should turn to goodness and spirituality, and the need to improve spiritual and moral values in the professional activities of future social educators is being identified in the process of teaching. Analyzing the scientific-methodological foundations of the problem of improving the professional activities of future social pedagogues, he carried out M. Rokich’s "Value orientations" methodology and carried out work on the differentiation of subjects in the educational program for the training of social pedagogues. According to the results obtained from the empirical research, it is shown that there are differences between the values between the 1st and 3rd year students according to the terminal values and instrumental values index. We believe that the article will be interesting for social pedagogues, teachers and students of pedagogical higher education institutions, and scientists studying the problem of spiritual and moral values.